Connotative electronic dictionaries and connotative system - N A Pavlyuk (RUDN Journal of Language Studies, Semiotics and Semantics, 2012)
The article is devoted to the principles of the creation of electronic connotative dictionaries and prospects for their use. There are some algorithms that describe system connotative links in the vocabulary, including specific concepts: connotative antonyms, metaphor, polysemy. It also involves the capabilities of the comparative analysis of connotative models for different ethnic groups.